Physical, mechanical, and microstructural characterization of novel, 3D-printed, tunable, lab-grown plant materials generated from Zinnia elegans cell cultures. (April 2022) - Beckwith, Ashley L.; Borenstein, Jeffrey T.; Velásquez-García, Luis F.
Graphical abstract: Abstract: To date, wood has been viewed as an attractive commodity because of its low relative cost and widespread availability. However, supply is increasingly strained, and, in many ways, trees make a non-ideal feedstock—with slow, climate and seasonally dependent growth, low yields of high-value products, and susceptibility to pests and disease. Recent research offered an approach to generate plant-based materials in vitro without needing to harvest or process whole plants, thereby enabling: localized, high-density production, elimination of energy-intensive collection and hauling, reduced processing, and inherent climate resilience. This work reports the first physical, mechanical, and microstructural characterization of 3-D printed, lab-grown, and tunable plant materials generated with Zinnia elegans cell cultures using such methodology. The data show that the properties of the resulting plant materials vary significantly with adjustments to hormone levels present in growth medium. In addition, configuration of the culture environment via bioprinting and casting enables the production of net-shape materials in forms and scales that do not arise naturally in whole plants. Finally, new comparative data on cell development in response to hormone levels in culture medium demonstrates the repeatability of growth trends, clarifies the relationship between developmental pathways, and helps to elucidate the relationships between cellular-level culture characteristics and emergent material properties.